2020
DOI: 10.1002/ams2.603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non‐pharmaceutical interventions for the COVID‐19 pandemic on emergency department patient trends in Japan: a retrospective analysis

Abstract: The coronavirus disease (COVID-19) pandemic massively impacted emergency department (ED) visits. The unavailability of specific therapies or vaccines has made non-pharmaceutical interventions (NPIs) an alternative strategy for COVID-19. We assessed the impact of NPIs (nationwide school closures and state of emergency) on ED visits during the COVID-19 pandemic in Japan. Methods: This retrospective study compared the trends in ED visits from 1 January to 25 May, 2020 (during the pandemic) with the average during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…1 As a result, traffic accidents, labor-related accidents, and sports-related injuries decreased under the state of emergency. [2][3][4][5] In contrast, many hospitals in areas affected by the COVID-19 pandemic restricted their provision of emergency medical care due to the countermeasures against nosocomial infection or the redistribution of limited human resources, which made emergency transportation to hospitals more difficult. 3 Many studies have dealt with mild-to-moderate trauma patients under the COVID-19 pandemic, but few have addressed major trauma.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result, traffic accidents, labor-related accidents, and sports-related injuries decreased under the state of emergency. [2][3][4][5] In contrast, many hospitals in areas affected by the COVID-19 pandemic restricted their provision of emergency medical care due to the countermeasures against nosocomial infection or the redistribution of limited human resources, which made emergency transportation to hospitals more difficult. 3 Many studies have dealt with mild-to-moderate trauma patients under the COVID-19 pandemic, but few have addressed major trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[ [1] , [2] , [3] , [4] ] A systematic review including multiple countries concluded that the introduction of non-pharmaceutical interventions, aimed to reduce COVID transmission, also resulted in reduced flu burden. [ 5 ] Reductions in overall ED visits have also been reported following the pandemic and the public health measures in place, in Japan [ 6 ] and in the US. [ 7 ] Such reduction was also documented in pediatric ED visits.…”
Section: Introductionmentioning
confidence: 99%
“…We applaud Lai et al in this Letter to the Editor for exploring changes in acute care utilization in Taiwan related to COVID-19. Their result, that ED visits fell by between 21.3% and 36.3% compared to prior years during the Lunar New Year Holiday in 2020, and that they fell by even larger margins for influenza-like-illnesses, is comparable to findings from the United States [ 1 , 2 ], the UK [ 3 ], and Japan [ 4 ]. In Taiwan, COVID-19 control measures likely contributed to a change in the baseline population incidence of pathologies with infectious etiology.…”
mentioning
confidence: 70%